Transforming serayu sediment into compost-amended medium for soybean cultivation - Suyadi, Aman; Suratman, Didit Agustinus; Pribadi, Teguh (Asian Journal of Agriculture and Rural Development, 2025)
River sediment accumulation poses both environmental and management challenges in tropical watersheds; however, these sediments possess physicochemical properties that can be valorized for agricultural use through appropriate amelioration. This study evaluated the potential of Serayu River sediment from three sites: Somagede, Banyumas, Kebasen (Indonesia) as a growing medium for soybean (Glycine max L. Merril) cultivation. Twelve sediment-based media were formulated by combining sediment with compost, zeolite, and biochar in different ratios and tested in a completely randomized design with three replications. The sediments exhibited sandy clay loam to clay loam textures, neutral pH (7.60–7.66), but low organic matter (1.69–2.40%) and nutrient contents. Compost amendment substantially improved media fertility and crop performance, whereas zeolite and biochar treatments produced moderate responses. The best results were obtained from compost-amended treatments M3 (sediment: compost = 3:1) and M6 (1:1), which increased plant height by 17–19%, stem diameter by 61–74%, and filled pod number by 51–61% compared with the control. Principal component analysis confirmed that compost treatments consistently clustered within the high-performance quadrant, demonstrating synergistic effects on vegetative and reproductive traits. These findings indicate that compost-enhanced sediment can serve as a sustainable alternative growing medium, addressing sediment disposal issues and improving soil fertility for legume production. The study highlights a viable pathway for circular agriculture and sustainable sediment management in tropical river basins, with future research recommended to include heavy metal assessment, multi-season field validation, and biological inoculation for optimizing nitrogen fixation.